2017
DOI: 10.1186/s41100-017-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between fluid removal and number of B-lines, peak early mitral inflow wave velocity, and inferior vena cava dimensions in hemodialysis patients

Abstract: Background: The inferior vena cava (IVC) dimensions represent the right ventricular preload, whereas the peak early mitral inflow wave velocity (peak E-velocity) represents the left ventricular preload. On the other hand, B-lines represent extravascular lung water. The aim of this study was to evaluate possible acute changes in the IVC dimensions, peak E-velocity, and number of B-lines during hemodialysis therapy. Methods: A total of 55 consecutive patients receiving maintenance hemodialysis were enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…On the other hand, B-lines represent extravascular lung water. We previously reported that the IVC dimensions and the peak E-velocity were reduced mainly during the first half of the dialysis period, while the number of B-lines, which represents lung congestion, decreased significantly mainly during the last half of the dialysis period [18]. This finding may be largely dependent on the time lag in plasma refilling.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, B-lines represent extravascular lung water. We previously reported that the IVC dimensions and the peak E-velocity were reduced mainly during the first half of the dialysis period, while the number of B-lines, which represents lung congestion, decreased significantly mainly during the last half of the dialysis period [18]. This finding may be largely dependent on the time lag in plasma refilling.…”
Section: Discussionmentioning
confidence: 89%
“…The decrease in oncotic pressure due to low serum level of albumin causes the movement of water from intravascular to lung interstitial. The malnutrition-inflammation-atherosclerosis syndrome affects mortality and hydration mechanics [18], which may be another cause of the relation between number of B-lines and mortality. The relationship between the number of B-lines and mortality has been reported by investigators in several countries.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, B-lines represent extravascular lung water. We previously reported that the IVC dimensions and peak E-velocity decrease mainly during the first half of the dialysis session, while significant decrease in the number of B-lines, which reflects lung congestion, is observed mainly during the latter half of the dialysis session [18]. This finding may be largely dependent on the time lag in plasma refilling.…”
Section: Discussionmentioning
confidence: 90%
“…The chest wall was divided into 8 areas (2 anterior and 2 lateral areas per side), and each of these areas was scanned [16]. The number of B-lines was counted as described in a previous report [17][18][19]. A cardiologist, who is blind to the result of blood peripheral blood sample, performed echocardiography test.…”
Section: Methodsmentioning
confidence: 99%
“…The meta-analysis incorporated 13 studies 6,7,18-28 of the included 33 studies, while the other 20 studies, lacking sufficient numerical data, were included for qualitative analysis as part of the systematic review. 9,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Study Selectionmentioning
confidence: 99%